Effect of previous strength training episode and retraining on facilitation of skeletal muscle hypertrophy and contractile properties after long-term detraining in rats - Lee, Sukho; Hong, Kwang-Seok; Kim, Kijeong (Journal of exercise rehabilitation, 2016)
In the present study, we investigated the effects of previous strength training and retraining following long-term cessation of exercise on muscle mass and contractile properties. Female Sprague-Dawley rats (n=24) aged eight weeks were randomly assigned one of the four groups: control (CON), detraining (DT), training (TR), and retraining (RT). The training regimen consisted of climbing ladder 5×3 sets, once every third day for eight weeks with weight attached to the tail. The weight carried during each training session was initially 50% of body weight and progressively increased by 10% per session. The rats in DT were detained for 20 weeks followed by eight weeks strength training. The rats in the both TR and RT groups underwent eight weeks training. DT was age matched new training group while RT was retraining group af-ter 20 weeks of detraining. Soleus, gastrocnemius, tibialis anterior, and flexor hallucis longus (FHL) muscles were harvested in order to mea-sure the weight, and in situ contractile properties of FHL were mea-sured including specific twitch tension (Spt) and specific tetanic tension (Spo). TR showed significant increase in muscle mass compared to CON (P<0.05). DT and RT showed significant increase in muscle mass when compared to all other groups (P<0.05). There was no statistical difference in Spt and Spo among the groups. The present study showed that previous strength training facilitates retraining-induced muscle hy-pertrophy following long-term cessation of exercise.